The Determinant of Market-Based Performance: Evidence from Manufacturing Companies in Indonesia - Tikasari, Nopi; Surjandari, Dwi Asih (Richtmann Publishing, 2020)
The research aims to explore the determinant of firm’s market-based performance in Indonesia manufacturing companies, listed in Indonesia Stock Exchange between 2014 to 2019. The proxies used in this research are Return on Equity (ROE), Leverage, Earning per Share (EPS), Growth, Liquidity (Liquid) and Non-Debt Tax Shield (NDTS). The sampling method employs purposive sampling while the analysis is performed using E-views version 11. The result indicates that in partial, Leverage is negatively significant affect to Firm Performance while the other measured variables, namely Return on Equity, Leverage, Earning Per Share, Liquidity and Non-Debt Tax Shield, prove to be insignificant affect to firm performance. All variables simultaneously affect strongly on Firm Performance. This research implies that the management of the firm should observe Return on Equity (ROE), Leverage, Earning- per Share (EPS), Growth, Liquidity (Liquid) and Non-Debt Tax Shield (NDTS) closely in developing their strategy for better firm performance.